Guideline review: EASL clinical practice guidelines: drug-induced liver injury (DILI). Issue 4 (29th July 2021) - Brennan, Paul N; Cartlidge, Peter; Manship, Thomas; Dillon, John F
Abstract : The European Association for the Study of the Liver has produced extensive guidelines for the investigation and management of drug-induced liver injury. Here, we provide a commentary and overview of some of the principle disease investigations and management that arise from these guideline recommendations.